INVESTIGATION OF THE INFLUENCE OF THE NUMBER OF REPETITIONS ON THE PROCESS OF LASER MARKING OF HS6-5-2-5 STEEL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Today, methods for marking parts and components in industrial production are constantly improving, and they must meet several basic criteria for active traceability by consumers. The parameter that is of paramount importance for the quality of the marking is related to the contrast of the marked sign or QR code. To achieve optimal contrast, a number of technological factors and the functional relationships between them must be taken into account.The report examines the role of the number of repetitions on contrast in raster marking of HS6-5-2-5 tool steel products. The dependences of the number of repetitions on the speed and frequency are also taken into account - the main factors in the process of laser ablation. Graphs of the depth of the marking are drawn depending on the number of repetitions and the linear density of the pulses. The experiments were made with a fiber laser. By the performed analyses the working intervals of processing between the studied factors are deduced, allowing to achieve the desired optimal result.